Is an Energy Surplus Required to Maximize Skeletal Muscle Hypertrophy Associated With Resistance Training - Slater, Gary John; Dieter, Brad P.; Marsh, Damian James; Helms, Eric Russell; Shaw, Gregory; Iraki, Juma (Frontiers in Nutrition, 2019)
The rate and amount of muscle hypertrophy associated with resistance training is influenced by a wide array of variables including the training program, plus training experience, gender, genetic predisposition and nutritional status of the individual. Various dietary interventions have been proposed to influence muscle hypertrophy, including manipulation of protein intake, specific supplement prescription, and creation of an energy surplus. While recent research has provided significant insight into optimisation of dietary protein intake, the specific energy surplus required to facilitate muscle hypertrophy is unknown. However, there is clear evidence of an anabolic stimulus possible from an energy surplus, even independent of resistance training. Common textbook recommendations are often based solely on the assumed energy stored within the tissue being assimilated. Unfortunately, such guidance likely fails to account for other energetically expensive processes associated with muscle hypertrophy, the acute metabolic adjustments that occur in response to an energy surplus, or individual nuances like training experience and energy status of the individual. Given the ambiguous nature of these calculations, it is not surprising to see broad ranging guidance to energy needs. These estimates have never been validated in a resistance training population to confirm the ‘sweet spot’ for an energy surplus that facilitates optimal rates of muscle gain relative to fat mass. This review not only addresses the influence of an energy surplus on resistance training outcomes, but also explores other pertinent issues, including ‘how much should energy intake be increased’, ‘where should this extra energy come from’, and ‘when should this extra energy be consumed’. Several gaps in the literature are identified, with the hope this will stimulate further research interest. Having a broader appreciation of these issues will assist practitioners in the establishment of dietary strategies that facilitate muscle strength and hypertrophy associated with resistance training while also addressing other important nutrition related issues such as optimisation of fuelling and recovery goals. Practical issues like the management of satiety when attempting to increase energy intake are also addressed.